Applied Linguistics: Its nature and scope - James, Carl (Journal of Modern Languages, 2017)
My ambition today is to specify in outline what doing applied Linguistics (AL) and being an applied linguist involves. To this end, I shall first attempt to define the field of AL, and secondly to distinguish AL from linguistic theory on the one hand and from pedagogic practice (didactics) on the other, suggesting that AL occupies an interface position mediating between these two. My hope is that readers will recognise their own familiar practices in the descriptions I offer.